Psoriatic erythroderma after systemic corticosteroid therapy: case report - Kopeć, Karolina; Jagas, Anna; Jankowska-Konsur, Alina; Maj, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Erythroderma (exfoliative dermatitis) is an acute, generalized inflammation of the skin, which affects at least 90% of its surface. It is a life threatening illness in the course of which various types and degrees of scaling and itching are observed. The main causes of erythroderma are psoriasis, atopic dermatitis, drug reactions, mycosis fungoides and pityriasis rubra pilaris. Psoriatic erythroderma is classified as a secondary erythroderma. It may develop spontaneously or more often as a result of incorrect treatment. Objective. To present side effects of oral corticosteroids administration in a patient with psoriasis. Case report . A 36-year-old woman, suffering from psoriasis for over 7 years, was admitted to the hospital in March 2011 due to exacerbation of skin lesions up to erythroderma after administration of oral corticosteroid therapy. Three weeks after corticosteroids withdrawal, significant worsening of the disease was observed. On admission she presented massive skin inflammation, scaling and itching. Laboratory tests revealed increased markers of inflammation. The patient was treated with combined immunosuppressive therapy and topical ointments. After 3 weeks, significant regression of skin lesions and normalization of laboratory tests were observed. Conclusions . Psoriasis is a common cause of erythroderma in adults. Although in Europe the disease affects about 2% of the population and knowledge of its treatment should be common, cases of systemic administration of corticosteroids in patients with psoriasis in the treatment of the underlying disease or of the comorbidities are still being reported.